BREEDING OF WINTER WHEAT ON TOLERANCE TO LEAF RUST (PUCCINIA TRITICINA ERIKS.) IN MOSCOW RIA “NEMCHINOVKA” - B. I. Sandukhadze; M. I. Rybakova; G. V. Kochetygov; A. A. Morozov; E. K. Sandukhadze; V. V. Bugrova (Зерновое хозяйство России, 2018)
The genes of P.triticina tolerance of the varieties of soft winter wheat have been studied by test-isolators. The experiment was based on Flor’s theory ‘gene for gene’, when a tolerant gene matches virulence. Eleven varieties and promising lines bred by Moscow RIA “Nemchinovka” and seven ones bred in other regions were studied. The study was carried out on twelve monogenic lines with Thather with genes Lr 2a, Lr 2b, Lr 9, Lr 11, Lr 15, Lr 16, Lr 20, Lr 23, Lr 26, Lr 36, Lr 44, Lr 46 and 10 test-isolators with P. triticina with different virulence and of various origin. If its reaction to test-isolator coincides with the reaction of monogenic line of the gene it’s a sign of presence or absence of a definite tolerant gene to P. triticina in the variety. It’s impossible to determine a definite gene if there is a match of reactions to all isolators or there isn’t. The use of PCR-analysis with CSLV 34 allowed identifying some genes. Promising lines ‘Eritrospermum 1066/08’ and ‘Eritrospernum 1068/08’ possess the gene 34, which gives aging stability; ‘Eritrospernum 1068/08’ possesses an additional gene 3a. The varieties ‘Nemchinovskaya 17’ and ‘Nemchinovskaya 24’ possess the gene Lr 9, the varieties ‘Donshchina’ and ‘Snezhana’ possess the gene Lr 26, the variety ‘Doka’ possesses the genes Lr 20 and Lr 23 with an unknown one, the variety ‘Gene’ possesses the gene Lr 46 with two unknown ones.  The varieties ‘Nemchinovskaya 17’ and ‘Nemchinovskaya 24’with the genes Lr 9 and Lr 46, which slow the development of the disease in the field conditions and the varieties KS 93 U11 and KS 93 U50 should be used breeding on tolerance to leaf rust.  The gene Lr 9 was identified by PCR-analysis in F₂ and F₃ of the varieties ‘Nemchinovskaya 17’ and ‘Nemchinovskaya 24’ hybridized with ‘Moskovskaya 40’, having a high content of protein. It showed a possibility to obtain varieties with leaf rust tolerance and high quality.